Development of chromenoquinoline-fused coumarin dyes and their application in bioimaging. (September 2022) - Tian, Rumeng; Ren, Xiaojie; Niu, Peixin; Yang, Lei; Sun, Ailing; Li, Yuhan; Liu, Xingjiang; Wei, Liuhe
Abstract: In this work, a series of new dyes, CQ-Cou, with a newly prepared chromophore acquired by hybridizing classic coumarin with chromenoquinoline, are designed and synthesized for the first time. We systematically investigated the photophysical properties of these chromenoquinoline-fused coumarin dyes and found they have the properties of relatively high fluorescence quantum yield, high photostability and molar absorption coefficient. Furthermore, the mechanisms of intramolecular charge transfer (ICT) related to donor and acceptor in these chromophores were researched by the theoretical calculations using density functional theory (DFT) and time-dependent density functional theory (TD-DFT). Importantly, the successful application of these new dyes in biological imaging for living cells and zebrafish is demonstrated. Graphical abstract: Image 1 Highlights: A family of chromenoquinoline-fused coumarin dyes were developed for the first time. The tunability of the optical properties for CQ-Cou dyes was realized. The application of these new dyes in bioimaging was demonstrated.